Interactive Association Between CYP2C9 rs2860905 Polymorphism and Atrial Fibrillation on Ischemic Stroke in Taiwan Biobank Participants - Peng JW; Nfor ON; Ho CC; Hsu SY; Lung CC; Tantoh DM; Chou MC; Liaw YP (Dove Medical Press, 2021)
Jui-Wen Peng,1 Oswald Ndi Nfor,2 Chien-Chang Ho,3,4 Shu-Yi Hsu,2 Chia-Chi Lung,2 Disline Manli Tantoh,2,5 Ming-Chih Chou,1 Yung-Po Liaw2,5 1Institute of Medicine, Chung Shan Medical University, Taichung, 40201, Taiwan; 2Department of Public Health and Institute of Public Health, Chung Shan Medical University, Taichung, 40201, Taiwan; 3Department of Physical Education, Fu-Jen Catholic University, New Taipei City, 24205, Taiwan; 4Research and Development Center for Physical Education, Health, and Information Technology, Fu Jen Catholic University, New Taipei, 24205, Taiwan; 5Department of Medical Imaging, Chung Shan Medical University Hospital, Taichung City, 40201, TaiwanCorrespondence: Yung-Po LiawDepartment of Public Health and Institute of Public Health, Chung Shan Medical University, No. 110, Sec. 1 Jianguo N. Road, Taichung, 40201, TaiwanTel +886424730022 ext. 11838Fax +886423248179Email Liawyp@csmu.edu.twMing-Chih ChouInstitute of Medicine, Chung Shan Medical University, No. 110, Sec. 1 Jianguo N. Road, Taichung, 40201, TaiwanTel +886424730022 ext. 11191Fax +886423248130Email juhan0223@yahoo.com.twPurpose: Ischemic stroke accounts for approximately 85% of all strokes. Risk factors include atrial fibrillation, metabolic disorders, and genetic and lifestyle factors. There is limited evidence to support the association between atrial fibrillation and the risk of ischemic stroke based on genetic variants. We assessed the relationship between ischemic stroke and atrial fibrillation among participants in Taiwan Biobank (TWB) based on the rs2860905 variant of the cytochrome P450 Family 2 Subfamily C Member 9 (CYP2C9) gene.Materials and Methods: Using logistic regression analysis, we estimated the odds ratios (OR) and 95% confidence intervals (CI) for ischemic stroke among 17,726 biobank adults recruited from 2008 through 2015.Results: Of the eligible participants (n = 17,726), 906 were identified with ischemic stroke. Atrial fibrillation was positively associated with ischemic stroke (OR=3.70; 95% CI, 2.21- 6.20), whereas the rs2860905 variant was not. The OR for ischemic stroke among those with GA/AA genotype was 1.00 (95% CI, 0.82- 1.22) compared to those with the GG genotype. Based on the genotype-stratified analysis, the OR for ischemic stroke was 4.68 (95% CI, 2.70- 8.09) among individuals with GG genotype who had atrial fibrillation compared to those who did not.Conclusion: These results demonstrate that the GG genotype of the CYP2C9 rs2860905 variant appears to enhance the risk of ischemic stroke among adults in Taiwan. It could be essential to factor this genotype-specific contributor to ischemic stroke into clinical and experimental investigations of the disease in Taiwan.Keywords: genetic variation, risk prediction, stroke